Disconnected N-doped zigzag ZnO nanoribbon for potential Negative Differential Resistance (NDR) applications. (September 2021) - Krishna, M. Sankush; Singh, Sangeeta
Abstract: Quantum coherence and non-equilibrium statistics are the governing mechanisms for electronic transport in 2-D materials. The present work investigates the electronic transport properties of pristine and N-doped disconnected zigzag ZnO nanoribbons (Z-ZnONRs) using density functional theory (DFT) framework along with non-equilibrium Green's function (NEGF). Interestingly, even though the structures are disconnected, still they exhibit electron transport. These ZnONRs disconnected structures can act as two probe devices by deploying the tunneling mechanism for electron transport. It is reported that the tunneling current decreases with an increase in the disconnected distance between the two considered Z-ZnONR structures. Further, negative differential resistance (NDR) characteristics are observed in all the considered configurations. Moreover, the N atom doping is also studied at the disconnected edges. N-dopant position affects the I – V characteristics based on the dopant sites. Zn-rich edge dopant induces NDR across a wide range while O-rich edge dopant induces linear I – V behavior with lower NDR characteristics. The highest NDR peak-to-valley current ratio is reported around 5.6 × 1 0 4 within the 0.15 V bias region. The structure with N doped at both edges and disconnected distance as 0.5 Å exhibited dominant NDR behavior. This finds their potential use in the design of oscillators, switches, rectifiers, amplifiers, frequency converters, detectors, and resonator circuits, etc.